PENGARUH MOTIVASI BELAJAR DAN KEADAAN EKONOMI KELUARGA TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MADRASAH ALIYAH DARUL ULUM KUBU RAYA - Kulsum, Kulsum; Aminuyati, Aminuyati; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study "the effect of learning motivation and family socio-economic conditions on learning outcomes of class XI IPS Madrasah Aliyah Darul Ulum Kubu Raya" This research was conducted using a descriptive method using a quantitative approach. The research technique used is direct communication techniques and documentary study techniques with data collection tools in the form of questionnaires and documentation. based on R Square shows that the learning motivation and social economic condition of the students' families affect the learning outcomes of class XI IPS at Madrasah Aliyah Darul Ulum Kubu Raya by 1.31% with a t-count value of 6.125 and a significance value (sig). A total of 0,000. The value of t count (6.152) t table (1.708) it can be stated that the hypothesis test Ho is rejected and Ha is accepted.)